Studi Eksperimental Pengaruh Parameter Pemakanan terhadap Kekasaran Permukaan Baja AISI 1045 pada Proses Pemesinan Bubut - Harahap, Jagodang; Maulidin, Maulidin; Saputra, Edi; Tanjung, Iqbal; Nasution, Arya Rudi (Rekayasa Material, Manufaktur dan Energi, 2026)
ABSTRACKThe quality of machining results in turning operations is strongly influenced by the surface finish produced. Surface roughness is a critical parameter for assessing machining performance as it directly affects wear resistance, efficiency, and the service life of components. Medium carbon steel AISI 1045 is widely applied in manufacturing industries, particularly for shafts, gears, and structural elements, due to its favorable mechanical properties. However, its surface finish is highly sensitive to machining parameters, making the selection of cutting conditions essential. This study aims to evaluate the effect of cutting speed and depth of cut on the surface roughness of AISI 1045 steel using conventional turning. Cylindrical specimens measuring Ø30 mm × 80 mm were machined with a carbide cutting tool under three cutting speeds (127, 225, and 510 rpm) and four depths of cut (0.2, 0.4, 0.4 and 0.6 mm). Surface roughness was measured using a Mitutoyo SJ-310 profilometer at four reference points, and the average Ra value was taken as the representative result. The findings reveal that the lowest cutting speed (127 m/min) combined with the smallest depth of cut (0.2 mm) produced the smoothest surface with Ra = 2.388 µm. In general, increasing cutting speed and depth of cut led to lowew roughness values, with the maximum recorded at 9.760 µm under certain extreme conditions. Several anomalies were also observed at high cutting speeds due to vibration and process instability. In conclusion, proper selection of machining parameters is crucial to achieving optimal surface quality while maintaining process efficiency. These results may serve as a practical reference for manufacturing industries in optimizing the turning of AISI 1045 steel.